(untitled) (Research, Society and Development, 2022)
Sodium hexametaphosphate (SHMP) is commonly used to control acidity, stabilize and retard gelatinization of dairy products and in the melting of cheeses in the manufacture of processed cheeses. This salt dissociates the casein micelles present in milk, sequestering calcium ions. In previous studies, SHMP was shown to be the most efficient in dissociating casein micelles compared to other calcium scavengers. Variations in temperature and pH affect the mineral-protein balance and electrostatic interactions, leading to the disruption of casein micelles. Since the turbidity of a colloidal suspension, such as that of casein micelles in milk, is related to the size and spreading properties of the dispersed particles, dissociations of casein micelles are expected to reduce the turbidity of milk. This review describes recently developed strategies to overcome challenges related to milk turbidity using SHMP, but does not present their use in the cheese industry (melters). Optimization of the best conditions of pH, temperature and concentration of SHMP, can bring a new methodology for the development of translucent beverages and overcome solubility problems of concentrated milks with high protein content.